EXPLORING RAMAN SPECTROSCOPY OF CNTs: INFLUENCE OF HOTWIRE TEMPERATURES ON RBM, D AND G BANDS USING HWC-VHF-PCVD - Abidin, Kurniati; Malago, Jasruddin D; Noor, Fatimah A.; Winata, Toto (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2025)
Carbon Nanotubes (CNTs) are nanostructured materials that offer mechanical, electrical, and thermal advantages, making them attractive for various technological applications. In this study, CNTs were synthesized using the Hot Wire Cell-Very High Frequency-Plasma Enhanced Chemical Vapor Deposition (HWC-VHF-PECVD) with hotwire temperature variation (225 °C, 275 °C, and 325 °C) as the main variable. Characterization of CNTs was conducted through Raman spectroscopy to evaluate the effect of hotwire temperature variation on the structure and quality of CNTs. The Raman test identified a characteristic RBM (Radial Breathing Mode) band around 100-300 cm⁻¹, a D-band around 1350 cm⁻¹ associated with structural defects, a G-band around 1580 cm⁻¹ indicating sp² carbon bonds, and a 2D-band around 2650-2700 cm⁻¹ associated with the graphitic layer stack. The quantitative analysis of Raman spectra showed ID/IG ratios of 0.94, 0.76, and 0.86 for CNTs synthesized at 225°C, 275°C, and 325°C, respectively, confirming that CNTs grown at 275°C exhibit the lowest structural disorder and highest graphitic crystallinity. The results show that the intensity of the G-band at 275°C hotwire temperature is higher than that at 225°C and 325°C, indicating better CNTs quality at this temperature. In addition, the Raman shift in the RBM-band for 275°Chotwire temperature is higher compared to 225°C and 325°C, indicating a variation in the diameter of the synthesized CNTs. This characterization reveals that the control of hotwire temperature greatly affects the structure and quality of CNTs, which is important for the optimization of the synthesis process and its application in the future.